Application of Think Pair Share (TPS) Media-Assisted Cooperative Learning Model in Pancasila Education Learning for Grade V Students - Yunianti, Widta Puji; Sofiarini , Andriana; Egok , Asep Sukenda (Civiliza Publishing, Indonesia., 2025)
Learning is a series of learning activities that involve teachers and students. Learning can create a teacher-to-student interaction to improve student competence. This study aims to determine the completeness of learning outcomes in Pancasila Education learning for grade V students of SD Negeri 46 Lubuklinggau after applying a Think Pair Share type cooperative learning model assisted by Flash Card media. The population in this study is all grade V students of SD Negeri 46 Lubuklinggau. Sampling was done using random sampling techniques. Data collection is carried out by test. The data were analyzed using a t-test at a significant level of α = 0.05. The results of the study showed that based on the data analysis that had been carried out, the average pre-test score was 45,455 and the average post-test test score was 84,242, so that there was an increase in student learning outcomes of around 38,787 after the implementation of the Think Pair Share type cooperative learning model assisted by Flash Card media. Based on the t-test analysis, a t-table value of ≥ was obtained, which was 1,817 ≥ 1,714. This means that Ho is rejected and Ha is accepted, so it can be concluded that the hypothesis in this study is acceptable. In other words, the learning outcomes of Pancasila Education students in grade V of SD Negeri 46 Lubuklinggau were significantly completed after the implementation of the Think Pair Share (TPS) type cooperative learning model assisted by Media Flash Card.